If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -4(5t + -17) = -69 Reorder the terms: 3 + -4(-17 + 5t) = -69 3 + (-17 * -4 + 5t * -4) = -69 3 + (68 + -20t) = -69 Combine like terms: 3 + 68 = 71 71 + -20t = -69 Solving 71 + -20t = -69 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-71' to each side of the equation. 71 + -71 + -20t = -69 + -71 Combine like terms: 71 + -71 = 0 0 + -20t = -69 + -71 -20t = -69 + -71 Combine like terms: -69 + -71 = -140 -20t = -140 Divide each side by '-20'. t = 7 Simplifying t = 7
| (5w-6)(3-w)=0 | | 8.7-4.7(x+2.3)=7-3(x+4) | | 5(2x-6)=30 | | 4ab-2b-2a= | | (132x)7-14x=0 | | 7x-2(x-5)=5(x+1)+8 | | 5x-9=5x+30-39 | | x-7=11/2 | | 7x-7x=25 | | x=20xy | | (x+7)*(x+3)= | | y=31292e(-0.2x) | | y=31292e-(9) | | (x+7)-(x+3)= | | 180=(180-(2x+60))+(3x+10)+x | | y=31292e-(0.2x) | | 180=(-180+(2x+60))+(3x+10)+x | | (x+7)+(x+3)= | | 180=(-180+2x+60)+(3x+10)+x | | 180=2x+3x+-180+60+10 | | 5(x-2)+4(x+2)=14-4x | | 4+-9x=9x+-2 | | 6=3sqrt | | 8x=-4x+-3x | | -16(t^2+4t+5)=0 | | d=1/16*8^2 | | d=1/16*7^2 | | d=1/16*9^2 | | d=1/16*60^2 | | d=1/16*20^2 | | 180=78+y+1.5y | | -1(4+x)=14 |